Sustainability Initiatives at Shaqra University: A Holistic Approach to Environmental Responsibility - Alqurashi, Yousef (Universitas Diponegoro, 2025)
This paper presents a comprehensive evaluation of Shaqra University’s sustainability initiatives across infrastructure, water, energy, and education domains. Drawing on institutional data from 2021 to 2025, the study uses a mixed-methods approach combining quantitative indicators with implementation narratives. Key findings include the expansion of green space from 30,000 m² with plans to double by 2030, a five-stage wastewater treatment system enabling 65% reuse for irrigation, and a planned solar energy project expected to supply 22.6% of campus electricity upon completion. Smart building systems currently cover over 38,000 m², and a GHG inventory is planned for 2026 to track Scopes 1 and 2 emissions. The university’s academic mission supports sustainability through 43 sustainability-related courses, five active student teams, over 1,600 volunteer hours, and more than 1.3 million in funded research. These efforts reflect Shaqra University’s integrated institutional model for environmental responsibility, combining planning, operations, and education in alignment with Vision 2030, the Saudi Green Initiative, and the SDGs. The findings offer a roadmap for universities in arid and semi-arid regions seeking to institutionalize sustainability.